(BeDABCO)2Pd2Cl6 as an efficient homogeneous catalyst for copper‐free Sonogashira cross‐coupling reaction. (20th June 2014) - Hajipour, Abdol R.; Rafiee, Fatemeh
<x xml:space="preserve">Abstract</x> An efficient catalytic system using 1‐benzyl‐4‐aza‐1‐azoniabicyclo[2.2.2]octane chloride and palladium chloride ((BeDABCO)2Pd2Cl6) was developed for the Sonogashira reaction. In the presence of a catalytic amount of this efficient, stable homogeneous catalytic system that is non‐sensitive to air and moisture, various aryl halides were efficiently coupled with phenylacetylene in good yields in H2O at 50°C under copper‐free conditions. Benzyl dabco as an efficient ligand and also a quaternary ammonium salt had an efficient stabilizing effect on the Pd(0) species. Copyright © 2014 John Wiley & Sons, Ltd.